Ukryte wartościowanie. Kategoria męskoosobowości z perspektywy osób uczących się języka polskiego jako obcego - Łukaszewicz, Barbara (Neofilolog, 2026)
There is a noticeable lack of research in Polish glottodidactics concerning the causes of language errors from the perspective of foreign learners. This is particularly important in areas known as “difficult spots in Polish,” such as masculine personal gender, which leads to frequent learner mistakes. Based on a survey conducted among 100 foreigners learning Polish at levels B1–C2, and using categorization of open-ended responses, an attempt was made to answer the following questions: Does the correct formation of masculine personal plural forms contribute to effective communication, and why? Do foreign learners pay attention to using correct masculine personal plural forms in (1) spoken and (2) written communication, and why? Are foreign learners aware that incorrect masculine personal plural forms can carry negative connotations, and what are their opinions on this issue? What difficulties do foreign learners encounter when forming masculine personal plural forms? The results indicate that respondents perceive a relationship between the correct use of these forms and effective communication. They tend to pay attention to avoiding mistakes, especially in written rather than in spoken communication. The majority are unaware that incorrect forms may be perceived as offensive or arrogant.